Enriched sensory feedback delivered during a voluntary action boosts subjective time compression - Ueda, Sayako; Shimoda, Shingo (Frontiers in Psychology, 2023)
The subjective experience of time can be influenced by various factors including voluntary actions.In our previous study, we found that the subjective time experience of an action outcome can be compressed when an individual performs a continuous action compared to a single action, suggesting that the sense of agency (SoA), the feeling of control over one's own action outcomes, contributes to the subjective time compression. We hypothesized that enhancing SoA by providing sensory feedback to participants would further compress the subjective time experience. To test this hypothesis, we used a temporal reproduction task where participants reproduced the duration of a previously exposed auditory stimulus by performing a voluntary action with varying auditory feedback. We examined how the subjective temporal experience of action outcomes and SoA were affected by the change in auditory feedback. Our results indicate that more enriched auditory feedback led to a greater degree of subjective time compression and a stronger sense of agency. This finding suggests the potential for developing new techniques to artificially compress the subjective time experience of daily events.